2013
DOI: 10.1111/ina.12055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relative humidity on the aerosolization and total inflammatory potential of fungal particles from dust-inoculated gypsum boards

Abstract: The aim of this study was to investigate the effect of relative humidity (RH) on the aerosolization and total inflammatory potential (TIP) of microbial particles released from gypsum boards inoculated with dust samples from homes. After microbial colonization, the gypsum boards were incubated at either high or low RH. The aerosolized particles (0.54-19.8 μm), culturable fungi, β-glucan and the TIP of the aerosolized particles were quantified. Despite the colonization of several fungal groups, Penicillium domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 51 publications
1
43
0
3
Order By: Relevance
“…7). Relative humidity and stocking density is shown to affect the aerosolization of fungal particulates343536, which in turn could affect the composition of airborne fungi. Whereas it has been shown that NH 3 is one of the main precursors of secondary PMs37, which could then affect the community structure of airborne fungi.…”
Section: Resultsmentioning
confidence: 99%
“…7). Relative humidity and stocking density is shown to affect the aerosolization of fungal particulates343536, which in turn could affect the composition of airborne fungi. Whereas it has been shown that NH 3 is one of the main precursors of secondary PMs37, which could then affect the community structure of airborne fungi.…”
Section: Resultsmentioning
confidence: 99%
“…This approach led to the discovery of submicronic fragments. Fungal biomarkers such as ergosterol (Rao et al 2005; Lau et al 2006; Menetrez et al 2009), phospholipid fatty acids (Womiloju et al 2003) and β -glucans (Rao et al 2005; Reponen et al 2007; Adhikari et al 2009; Madsen et al 2009; Singh et al 2011; Frankel et al 2013; Seo et al 2009, 2014) have also been used to demonstrate the presence of fungal biomass in various sizes of fungal aerosols. Further, enzymes, (e.g., chitinases [Madsen et al 2005, 2009; Madsen 2012]), antigens (Górny et al 2002) and allergens (Menetrez et al 2001) as well as mycotoxins (Sorenson et al 1987; Brasel et al 2005) have been used to demonstrate allergenicity and toxicity potential of various size fractions of the fungal aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…were subjected to air jets under controlled conditions (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). These particles have been suggested to be fungal fragments and important sources of allergens (16)(17)(18), antigens (7), (1¡3)-beta-D-glucans (19)(20)(21)(22)(23)(24)(25), and mycotoxins (26,27). Exposure to fungal submicronic particles may therefore provide an explanation for health effects observed in moldy indoor environments (28).…”
mentioning
confidence: 99%
“…Alternative approaches to characterizing fungal fragments have used the detection of fungal biomarkers, including (1¡3)-beta-D-glucans (10,19,21,23,25,29), N-acetyl-glucosaminase (23), fungal antigens (7), and mycotoxins (26,27), in the submicronic particle fractions (21,22,25,30,31). Some of these studies were confounded by imperfect size separation of the systems utilized since the presence of larger particles such as spores has been demonstrated in the assumed submicronic fraction (10,23,29).…”
mentioning
confidence: 99%